Aid to the Services Sector : Does It Affect Manufacturing Exports? - Ferro, Esteban (2012)
This paper evaluates the impact of foreign aid to five service sectors (transportation, information and communications technologies, energy, banking/financial services, and business services) on exports of downstream manufacturing sectors in developing countries. To address the reverse causality between aid and exports, the analysis relies on an original identification strategy that exploits (i) the variation of aid flows to service sectors, and (ii) the variation of service-intensities across industrial sectors and countries using input-output data. The authors find a positive effect of aid to services, in general, on downstream manufacturing exports of developing countries across regions and income-level groups.